FRI0331 COMPARISON OF THE THERAPEUTIC TRAJECTORIES OF PATIENTS WITH OLIGO AND POLYARTICULAR PSORIATIC ARTHRITIS. A REPORT FROM THE RHUMADATA® CLINICAL DATABASE AND REGISTRY. (2nd June 2020) - Choquette, D.; Choquette Sauvageau, L.; Bessette, L.; Ferdinand, I.; Haraoui, P.; Massicotte, F.; Pelletier, J. P.; Raynauld, J. P.; Rémillard, M. A.; Sauvageau, D.; Villeneuve, É.; Coupal, L.
Abstract : Background: Psoriatic Arthritis (PsA) most frequently presents as a polyarthritis or (less often) as an oligoarthritis [1]. Most of the patients in the original description of Moll and Wight had an oligoarticular presentation [2]. However, other studies have not found the same distribution in all patient populations [3]. Treatment response over time across presentation types has not been explored thoroughly in recent medical literature. Objectives: Using our proposed definition of oligo and polyarticular PsA status, based on the (rounded) mean of the first four available joint counts, we examine treatment sequences in each group. Methods: Data from patients participating in the RHUMADATA® clinical database and registry diagnosed with PsA were extracted on January 5 th, 2020. Joint count classification (oligo vs. poly) was assessed from the average of the first four available 66/68 joint counts. Patients were classified as having a polyarticular form of PsA if the (rounded) average, five or more of their joints were assessed as being swollen and/or tender. Subjects with four or less swollen or tender joints were classified as patients having oligoarticular PsA. Time spent treated with non-DMARDs, csDMARDs and bDMARDs, time to treatment (to csDMARDs and bDMARDs) and treatment selection were assessed from the entire PsA cohort. Continuous variables were tested using t-tests and binary variables using Fisher's exact test. Results: The data from all patients diagnosed with PsA (n=1029) was extracted from the RHUMADATA® clinical database and registry. All but 151 (15%) were classifiable, 470 (46%) were classified as oligoarticular PsA patients and 408 (39%) as polyarticular. Time from the first symptoms to the first clinic visit was 4.6 ± 6.5 years and 3.7 ± 6.6 (p-value=0.1311) years for the patients classified as oligo and poly respectively. A total oh 951 patients were treated with a csDMARD (144 of those could not be classified as oligo or poly). For those, time from diagnosis to first csDMARD (prior to any bDMARD) treatment was 1.7 ± 5.3 (oligo) years and 2.0 ± 7.0 (poly) years (p-value=0.4114). Methotrexate (MTX), hydroxychloroquine (HCQ) and leflunomide (LEF) were more frequently prescribed to polyarticular than oligoarticular PsA patients (MTX: 70% (poly) vs. 48% (oligo), p-value<.0001, HCQ: 41% vs. 25%, p-value <.0001, LEF: 17% vs. 8%, p-value<.0001, Sulfasalazine (SSZ): 17% vs. 19%, p-value=0.5232, Other csDMARDs: 5% vs. 4.5%, p-value=0.8688). A total of 648 patients were treated with a bDMARD (151 of those could not be classified as oligo or poly). For those, time from first csDMARD Rx to first bDMARD treatment was 6.3 ± 4.6 (oligo) years and 7.0 ± 4.7 years (p-value=0.0865). On average, over the entire treatment history, oligoarticular patients received 1.7 ± 1.2 biologic agents and polyarticular 2.0 ± 1.4, p-value=0.0110. bDMARDs were administered over 3.6 ± 3.6 years for oligo and 4.5 ± 3.9 years for poly, p-value=0.2122. Conclusion: Polyarticular PsA patients appear to be more aggressively treated than oligoarticular patients during the csDMARDs period. Although durations on bDMARDs are statistically similar, polyarticular patients change biotreatment more frequently. References: [1]Gladman DD, Ritchlin C, et al. Clinical manifestations and diagnosis of psoriatic arthritis. Update 2019. [3]Wright V, Moll JM. Psoriatic arthritis. Bull Rheum Dis 1971; 21:627. [3]Gladman DD. Psoriatic arthritis. Baillieres Clin Rheumatol 1995; 9:319. Disclosure of Interests: Denis Choquette Grant/research support from: Rhumadata is supported by grants from Pfizer, Amgen, Abbvie, Gylead, BMS, Novartis, Sandoz, eli Lilly, , Consultant of: Pfizer, Amgen, Abbvie, Gylead, BMS, Novartis, Sandoz, eli Lilly, , Speakers bureau: Pfizer, Amgen, Abbvie, Gylead, BMS, Novartis, Sandoz, eli Lilly, , Loïc Choquette Sauvageau: None declared, Louis Bessette Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, Roche, Sanofi, UCB Pharma, Consultant of: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, Roche, Sanofi, UCB Pharma, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer, Sanofi, Isabelle Ferdinand Consultant of: Pfizer, Abbvie, Amgen, Novartis, Speakers bureau: Pfizer, Amgen, Paul Haraoui Grant/research support from: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, and UCB, Consultant of: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Janssen, Merck, Pfizer, Roche, and UCB, Speakers bureau: Pfizer, Speakers bureau: Amgen, BMS, Janssen, Pfizer, and UCB, Frédéric Massicotte Consultant of: Abbvie, Janssen, Lilly, Pfizer, Speakers bureau: Janssen, Jean-Pierre Pelletier Shareholder of: ArthroLab Inc., Grant/research support from: TRB Chemedica, Speakers bureau: TRB Chemedica and Mylan, Jean-Pierre Raynauld Consultant of: ArthroLab Inc., Marie-Anaïs Rémillard Consultant of: Abbvie, Amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Paid instructor for: Abbvie, Amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Speakers bureau: Abbvie, Amgen, Eli Lilly, Novartis, Pfizer, Sandoz, Diane Sauvageau: None declared, Édith Villeneuve Consultant of: Abbvie, Amgen, BMS, Celgene, Pfizer, Roche, Sanofi-Genzyme, UCB, Paid instructor for: Abbvie, Speakers bureau: AbbVie, BMS, Pfizer, Roche, Louis Coupal: None declared